The Effectiveness Of Notaries Obligations In Providing Notarial Services Free Of Charge In Sragen Regency - Nurjayatun, Nurjayatun; Karjoko, Lego; Hermawan, Sapto (International Journal of Educational Research & Social Sciences, 2024)
A Notary Is A Professional Who Plays A Vital Role In Society, Particularly In Creating Order By Ensuring That Legal Events Are Documented In An Authentic Deed, In Accordance With Article 1, Paragraph (1) Of Law Number 2 Of 2014 On Amendments To Law Number 30 Of 2004 (Uujn). In Its Implementation, According To Its Authority Under Article 37, Paragraph (1) Of The Uujn, Which Mandates Notaries To Provide Notarial Services Free Of Charge To Those In Need, The Situation In Sragen Regency Remains Minimal. This Is Due To Several Factors That Hinder The Effectiveness Of This Article: 1) The Legal Factor Itself, Wherein Article 37 Of The Uujn Requires Further Clarification Regarding The Types Of Notarial Services That Can Be Provided Free Of Charge To Those Who Cannot Afford Them, In Order To Prevent Multiple Interpretations By Notaries And To Ensure Legal Certainty For All Parties Involved; 2) The Law Enforcement Factor, Specifically The Mpd (District Regulation Agency) And Notaries. In This Case, The Mpd Has Never Inquired Or Urged Notaries To Fulfill This Obligation, Which Is Based On Minimal Oversight From The Mpd. Furthermore, Notaries, Who Are Aware Of This Obligation, Have Never Conducted Legal Outreach To The Community, Resulting In A Lack Of Awareness Of The Regulation Among The General Public.